The Levant Reconciling a Century of Contradictions (American Journal of Islam and Society, 2012)
Although the revolution in Syria is unfolding within the modern politicalboundaries of this country, its proper understanding is not attainablewithout putting it in a larger historical context, which includes the adjacentgeographical areas of the Levant, Bilad al-Sham. Without such a broaderview, the appreciation of the complexity of the Syrian case is not possible,nor accounting for its consequences and anticipating its future.Probably, in no case, is the mess of colonial legacy more visible than itis in Syria. The pathway of this legacy marks the future development of thecountry, and its implications are facing the revolution today with arduouschallenges. The complexity of the Syria case is not limited to the politicaldimension; it is also complex at the meta-cultural level. Furthermore, thechange in Syria has consequences for the region as whole ‒ it will institutionalizethe Arab Spring as an unavoidable political force, and it will energizethe process of cultural reformation and the recovery of a civilizationalMuslim identity ...